Needs assessment and preparedness of the primary health care network for scaling-up preventive tuberculosis treatment in 5 Brazilian capitals - Dinah Carvalho Cordeiro; Pedro Kuabara; Bruna Chiarini Amaral; Lucas Maia Portugal; Daniel Souza Sacramento; Larissa Rodrigues de Oliveira; Jorgiane da Costa Ferreira Faria; Priscilla Wolter Paolino; Vanessa Cordeiro Vilanova; Mayara de Sá Cavalcanti de Melo; Cristina Bettin Waechter; Anete Trajman (PLoS ONE, 2025)
This study aims to conduct a needs and preparedness assessment of public primary care units to scale up tuberculosis infection diagnosis and tuberculosis preventive treatment in 5 Brazilian capitals. This observational operational study was carried out across five Brazilian high tuberculosis-burden cities. Clinics with at least one monthly new tuberculosis case were included. Data on Purified Protein Derivative (PPD) storage, tuberculin skin testing (TST) and interferon-gamma release assay (IGRA) availability, personnel qualified for performing TST, radiological facilities and tuberculosis preventive treatment drug availability, were gathered between August 2023 and January 2024. Out of 285 clinics included, 78% (CI95%: 73%−82%) did not offer TST on-site, with only 28% (CI95%: 22%3%) having staff qualified to perform TST, and 35% (CI95%: 29%−40%) lacking dedicated refrigerators for PPD storage. Most (97%, CI95%: 94%−99%) clinics did not collect IGRA testing, with an average distance of 6.7 km (CI95%: 5%−7%) to IGRA labs and a turnaround time of 11.7 days (CI95%: 9%13%) for results. Most (87%, CI95%: 83%−91%) do not offer on-site radiological testing. The primary care network was unprepared to scaling up tuberculosis infection testing. Key issues include unavailability of TST mainly because of insufficient qualified personnel. Without accelerated qualification of staff for TST, scaling up tuberculosis preventive treatment will be impossible.